Daredevil. Woman without fear - Zdarsky, Chip; Nocenti, Ann; Shalvey, Declan; Templeton, Ty; Giarrusso, Chris (Marvel Worldwide, Inc., 2022)
"Elektra is the world's deadliest assassin -- but when she took on the mantle of Daredevil, she took a vow not to kill, Now that solemn promise is about to be put to the ultimate test. Kraven the Hunter has Elektra dead in his sights, and he has no reservations about murder! Battered, bruised and with her back to the wall, can Elektra find a way to honor Matt Murdock's code? And if so, will the Woman Without Fear be strong enough to survive the unexpected consequences of mercy? Plus: Celebrate one hundred issues of Elektra with a giant-size celebration full of thrills, chills, surprises and all-out ninja action" -- Back cover.